2023
DOI: 10.1186/s12913-023-09508-2
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals discourses on men and masculinities in sexual healthcare: a focus group study

Abstract: Studies have reported that men’s uptake of sexual health services is low, that these services make them feel vulnerable, and that they experience sexual healthcare (SHC) as stressful, heteronormative, potentially sexualised and “tailored for women”. They also suggest that healthcare professionals (HCPs) working in SHC view masculinity as problematic, and situated in private relationships. This study aimed to explore how HCPs construct the gendered social location in SHC, specifically in terms of masculinity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Men’s lower mental health literacy could also mirror the gendered nature of the healthcare system. For example, two qualitative studies from Sweden recently found that healthcare personnel working with men’s sexual health often held traditional and stereotypical notions of masculinity, potentially reflected in their caregiving [ 67 ], and that the sexual healthcare in itself was constructed as a feminine and designed for women, which could discourage men from seeking care [ 68 ]. Research is needed to investigate if such gender bias exists also within the framing and organisation of the mental healthcare in Sweden, and how it may affect men’s mental health literacy, e.g., by reinforcing scepticism to the mental healthcare and its treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Men’s lower mental health literacy could also mirror the gendered nature of the healthcare system. For example, two qualitative studies from Sweden recently found that healthcare personnel working with men’s sexual health often held traditional and stereotypical notions of masculinity, potentially reflected in their caregiving [ 67 ], and that the sexual healthcare in itself was constructed as a feminine and designed for women, which could discourage men from seeking care [ 68 ]. Research is needed to investigate if such gender bias exists also within the framing and organisation of the mental healthcare in Sweden, and how it may affect men’s mental health literacy, e.g., by reinforcing scepticism to the mental healthcare and its treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This approach facilitates interaction and discussion amongst participants. For example, group members are able to consider and respond to points raised by others that they may not have thought of in an individual interview (Persson et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…54,55 However, the literature has also highlighted differing conclusions about the contribution of psychological interventions, potential aspects of risk among online communities and websites, and the need for an integrated multidisciplinary approach. 45,47,[56][57][58] A recent systematic review and meta-analysis 38 has demonstrated that psychosocial interventions contribute only to small improvements in distress and modest results on conception, indicating that future research is needed to refine available interventions to unique sources of stress, men and partners' preferences, and the experiences of individuals and dyads underrepresented in research, 59 while addressing barriers affecting timely referral to care. 60,61 "The decline in semen quality over the past 50 years is so universal and rapid that it cannot have a genetic basis but must be environmentally induced"…”
Section: Chiara Acquati Phd (Sexual and Reproductive Health Researcher)mentioning
confidence: 99%